Abnormal metabolism of shellfish sterols in a patient with sitosterolemia and xanthomatosis. - Gregg, R E (1986)
Sitosterolemia and xanthomatosis together are a disease characterized by premature cardiovascular disease, and by elevated plasma concentrations of total sterols and of plant sterols, especially sitosterol which is hyperabsorbed. In order to determine whether this abnormal metabolism also involved other sterols, a patient with sitosterolemia was fed a diet high in shellfish that contain significant quantities of noncholesterol sterols, some of which are less well absorbed than cholesterol in humans. Compared with control subjects (n = 8), the sitosterolemic subject had an increased absorption of 22-dehydrocholesterol (71.5% vs. 43.8 +/- 11.4%, mean +/- SD), C-26 sterol (80.6% vs. 49.3 +/- 11.4%), brassicasterol (51.8% vs. 4.8 +/- 4.2%), and 24-methylene cholesterol (60.5% vs. 16.0 +/- 8.3%). This enhanced absorption was associated with an increased plasma total shellfish sterol level (13.1 mg/dl vs. 1.9 +/- 0.7 mg/dl in normals). In the sitosterolemic subject, as in normals, the shellfish sterols were not preferentially concentrated in any lipoprotein class, and 50-65% of these sterols were in the esterified form in plasma. Bile acids and neutral sterols were quantitated in bile obtained by duodenal aspiration. The bile acid composition did not differ significantly in the sitosterolemic subject compared with the normal controls. The sitosterolemic subject, though, was unable to concentrate normally the neutral shellfish sterols in bile. The normal controls concentrated the shellfish sterols in bile 6.3 +/- 1.7-fold relative to the plasma shellfish sterol concentration whereas the study subject was only able to concentrate them 2.1-fold. We propose that sitosterolemia and xanthomatosis occur from a generalized abnormality in the usual ability of the gut mucosa and other tissues of the body to discriminate among many different sterols. This has important implications for the understanding of the pathophysiology of this disease and for therapeutic recommendations.